DETERMINAN HARGA SAHAM PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Susilowati , Handini Retno; Mulyani, Sri; Delima, Zamrud Mirah (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2023)
This study aims to determine the effect on the variable net profit margin, return on assets, earnings per share, and the current ratio on stock prices. The population in this study are banking companies listed on the Indonesia Stock Exchange in 2018-2021. This study used a quantitative research design and the data used were obtained from the annual financial reports of banking companies. The sampling technique used purposive sampling method with a total sample of 21 banking companies. The analytical method used is multiple linear regression analysis with SPSS version 25. The results of this study indicate that net profit margin has no effect on stock prices, return on assets has a negative effect on stock prices, earnings per share and current ratio have a positive effect on stock prices.